Cochrane Database of Systematic Reviews 2005
DOI: 10.1002/14651858.cd004025.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Music therapy for schizophrenia or schizophrenia-like illnesses

Abstract: Music therapy as an addition to standard care helps people with schizophrenia to improve their global state and may also improve mental state and functioning if a sufficient number of music therapy sessions are provided. Further research should address the dose-effect relationship and the long-term effects of music therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(29 citation statements)
references
References 32 publications
2
25
0
2
Order By: Relevance
“…Present research concluded that music has significant effect on behaviour disorders of intellectually disabled children, which is inconsistent with that of Grimm and Pefley (1990) who concluded that music helps children with learning difficulties, mental illness and intellectual disability. Gold et al, (2005) in a meta-analysis of four studies with merely moderate methodological quality, gave similar conclusion to that of present research that active music therapy may be more effective for clients with psychosis.…”
Section: Discussionsupporting
confidence: 87%
“…Present research concluded that music has significant effect on behaviour disorders of intellectually disabled children, which is inconsistent with that of Grimm and Pefley (1990) who concluded that music helps children with learning difficulties, mental illness and intellectual disability. Gold et al, (2005) in a meta-analysis of four studies with merely moderate methodological quality, gave similar conclusion to that of present research that active music therapy may be more effective for clients with psychosis.…”
Section: Discussionsupporting
confidence: 87%
“…Music therapy as an addition to standard care helps people with schizophrenia to improve their global state and may also improve mental state and functioning if a sufficient number of music therapy sessions are provided (Gold et al, 2005). Music therapy significantly diminished schizophrenic patients' negative symptoms, increased their ability to converse with others, reduced their social isolation, and increased their level of interest in external events (Tang, 1994).…”
Section: In Psychiatrymentioning
confidence: 99%
“…Gold et al [7] evaluated the effects of music therapy on people with schizophrenia, including schizophrenic disorders. This review was included in the Cochrane Library, a database constructed with systematic reviews of reports on clinical trials including randomized controlled trials.…”
Section: Music Therapy For Schizophrenic Patientsmentioning
confidence: 99%
“…Mössler et al [8] published an updated Cochrane review focusing on music therapy for people with schizophrenia. They reviewed 85 papers including papers that had been reviewed by Gold et al [7], and recognized eight reliable studies. They suggested that applying music therapy along with standard treatments was more effective in mitigating negative symptoms, depression, and anxiety, and improving general mental state and social functioning, than providing only standard treatments.…”
Section: Music Therapy For Schizophrenic Patientsmentioning
confidence: 99%